Implementation of Application Programming Interface (API) in Indonesian Dance and Song Applications - Bayu Priyatna; Aprilia Hananto (SYSTEMATICS, 2020)
The development of multimedia technology has become a phenomenon that cannot be contained. All technology platforms now use multimedia elements as GUI Interface because it makes it much easier for users to control it. The introduction of cultural customs such as Indonesian traditional dances and songs is critical so that it remains sustainable and is not undermined by foreign influences. A new and appropriate media is needed to socialize it, amicable and fun media for young children. Application of Application Programming Interface (API) in Indonesian death dance and song applications makes it easier to change data so that data flow mobility can be faster to change. The results of the research show that the implementation of API in the application has better effectiveness. and the white box test results show that the coding system can run according to function.